2005
DOI: 10.3354/meps296241
|View full text |Cite
|
Sign up to set email alerts
|

Daytime and nighttime vertical migrations of Alexandrium tamarense in the St. Lawrence estuary (Canada)

Abstract: A population of the toxic dinoflagellate Alexandrium tamarense was followed in a 48 h survey of the St. Lawrence estuary in order to determine its ability to perform vertical migrations in nature. A. tamarense performed daytime and nighttime migrations during our study. Cells were generally found close to the surface during daytime, started their descent down to the nitracline before sunset, and returned toward the surface after sunrise (with an estimated migration speed of 2 m h -1 ). Our results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…For example, Townsend et al (2001Townsend et al ( , 2005 reported both subsurface aggregations and bimodal distributions (indicative of AVM) of Alexandrium sp. in the Gulf of Maine when the MLD was between 20 and 30 m. A DVM signal was detected by Fauchot et al (2005) for the same species in the St. Lawrence estuary when the MLD was about 12 m. Laboratory experiments (MacIntyre et al 1997) have suggested that A. tamarense can change its VM strategies over a time scale of 1 to 2 d. These observations have been reproduced by our models and can be explained by several factors. First, dinoflagellates under different MLDs are likely to achieve different ANGR, which will influence both the choice of migration strategy and the cell densities in layers.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, Townsend et al (2001Townsend et al ( , 2005 reported both subsurface aggregations and bimodal distributions (indicative of AVM) of Alexandrium sp. in the Gulf of Maine when the MLD was between 20 and 30 m. A DVM signal was detected by Fauchot et al (2005) for the same species in the St. Lawrence estuary when the MLD was about 12 m. Laboratory experiments (MacIntyre et al 1997) have suggested that A. tamarense can change its VM strategies over a time scale of 1 to 2 d. These observations have been reproduced by our models and can be explained by several factors. First, dinoflagellates under different MLDs are likely to achieve different ANGR, which will influence both the choice of migration strategy and the cell densities in layers.…”
Section: Discussionsupporting
confidence: 69%
“…Eppley et al 1968, Watanabe et al 1991, MacIntyre et al 1997) and natural conditions (e.g. Eppley & Harrison 1975, Eppley et al 1984, Villarino et al 1995, Fauchot et al 2005. However, numerous studies have also suggested that the vertical profiles of many dinoflagellate species cannot be explained by a simple DVM pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The reorientation timescale, while known only for a handful of species 16,20,21,[27][28][29] , generally spans the range BB1-10 s, which, for typical turbulent dissipation rates (e ¼ 10 À 8 -10 À 6 m 2 s À 3 ), corresponds to CB1. Phytoplankton swimming speeds 30,31 , V C B100-1,000 mm s À 1 , are often comparable to or larger than the Kolmogorov velocities, V K B300-1,000 mm s À 1 , associated with these dissipation rates, suggesting F can often be of order unity. Thus, we expect that phytoplankton routinely inhabit regions of the [C, F] parameter space where patchiness is intense (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By such a swimming behaviour, cells could exploit the more nutrient-rich deeper waters during night and stay up in the light during the day (Cullen & Horrigan 1981, Villarino et al 1995, MacIntyre et al 1997, Fauchot et al 2005, Jephson et al 2011. Some dinoflagellates, like Gymnodinium bogoriense, start their upward migration towards the end of the dark period (Lieberman et al 1994), while for the raphidophyte H. akashiwo, upward swimming starts early in the light period (Bearon et al 2004), indicating that an endogenous rhythm (circadian clock) is involved.…”
Section: Positive Phototaxismentioning
confidence: 99%
“…Weise et al (2002) emphasized the link between precipitation, river runoff and blooms of the toxic dinoflagellate Alexandrium tamaranse in the St. Lawrence, Canada. However, long-lasting stra tification often leads to a nutrient-depleted euphotic zone above the pycnocline, conditions claimed to be a competitive advantage for dinoflagellates due to their swimming ability (MacIsaac 1978, Dortch & Maske 1982, Fauchot et al 2005, Jephson et al 2011). By DVM they are able to conduct photosynthesis near the surface during the day and exploit nutrientrich waters below the pycnocline at night (Eppley et al 1968, Cullen & Horrigan 1981, Raven & Richardson 1984, Olsson & Granéli 1991, Fraga et al 1992, Villarino et al 1995.…”
Section: Introductionmentioning
confidence: 99%